Comunicación del riesgo y respuesta pública: la exposición voluntaria ante marejadas en el borde costero del Gran Valparaíso, Chile - Vergara, Gonzalo; Handke, Michael (Revista de geografía Norte Grande, 2025)
Storm surges are a natural phenomenon threatening coastal populations, establishing a significant risk. This risk is constructed based on how, when and to whom they are communicated. Imprudent risk communication can preserve or even increase the perception of low risk. In this article, we analyze the communicative processes related to storm surge risk management in Greater Valparaiso, comparing the communication models of Shannon & Weaver (1948) and Westley & MacLean (1955). Through a content analysis of interviews, we present evidence of distortions in communication that encourage the voluntary exposure of the population, resident or floating, to storm surges. Consequently, term risk management. Finally, we discuss the implications of these distortions and narratives for more holistic risk governance aimed at increasing the resilience of the coastal population.
Veröffentlicht am 06. Januar 2025
Gesehen am 02.10.2025